2013
DOI: 10.1186/1743-0003-10-91
|View full text |Cite
|
Sign up to set email alerts
|

Review of fall risk assessment in geriatric populations using inertial sensors

Abstract: BackgroundFalls are a prevalent issue in the geriatric population and can result in damaging physical and psychological consequences. Fall risk assessment can provide information to enable appropriate interventions for those at risk of falling. Wearable inertial-sensor-based systems can provide quantitative measures indicative of fall risk in the geriatric population.MethodsForty studies that used inertial sensors to evaluate geriatric fall risk were reviewed and pertinent methodological features were extracte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
209
0
14

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 308 publications
(245 citation statements)
references
References 72 publications
3
209
0
14
Order By: Relevance
“…A previous study showed that frail elderly subjects exhibited significantly decreased smoothness in the sit-stand transition pattern [8,21,23,[29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study showed that frail elderly subjects exhibited significantly decreased smoothness in the sit-stand transition pattern [8,21,23,[29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…The stability and variability of walking can be identified by a simple control theory such as the Lyapunov exponent [22]. A review by Howcroft et al [8] suggested that intelligent computing methods such as neural networks and Bayesian classifiers might be more appropriate for fall risk classification than regression techniques [8]. However, no studies have identified the parameters that play the most important roles in the risk of falls.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inertial sensors consist of accelerometers and gyroscopes and directly measure angular velocity and linear acceleration of body segments, from which temporal and spatial gait parameters can 7 be measured (Howcroft et al, 2013). There were some disadvantages identified with the use of sensors, as they need to be routinely charged, and need to be wellpositioned and oriented or they can suffer from noise or drift.…”
Section: Advances In Technology: Quantifying the Timed Up And Gomentioning
confidence: 99%
“…Inertial sensors have the potential to provide a quantitative, objective, and reliable indication of falls risk in the geriatric population (Howcroft et al, 2013). The concept of this falls risk measurement involves the analysis of signals collected during movement via body-worn inertial sensors and the use of algorithms to predict falls risk (Shany et al, 2012).…”
Section: Falls Risk Estimate: Qtugmentioning
confidence: 99%